2012
DOI: 10.1109/tnsre.2011.2162851
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Muscle Model for Predicting Force and Energetics During Physiological Behaviors

Abstract: Muscles convert metabolic energy into mechanical work. A computational model of muscle would ideally compute both effects efficiently for the entire range of muscle activation and kinematic conditions (force and length). We have extended the original Virtual Muscle algorithm (Cheng , 2000) to predict energy consumption for both slow- and fast-twitch muscle fiber types, partitioned according to the activation process (E(a)), cross-bridge cycling (E(xb)) and ATP/PCr recovery (E(recovery)). Because the terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 60 publications
4
38
0
Order By: Relevance
“…For instance, as VL was prefatigued, an increase of the force produced by VL during Tlim appears to contradict an optimal control based on minimizing energy cost (Tsianos et al 2012). Interestingly, a similar observation has been reported by De Rugy et al (2012).…”
Section: Neurophysiological Interpretationssupporting
confidence: 64%
“…For instance, as VL was prefatigued, an increase of the force produced by VL during Tlim appears to contradict an optimal control based on minimizing energy cost (Tsianos et al 2012). Interestingly, a similar observation has been reported by De Rugy et al (2012).…”
Section: Neurophysiological Interpretationssupporting
confidence: 64%
“…As in Experiment 1, however, the muscle activation was well described by a simple linear rescaling of original patterns of activity, and not reoptimized for the novel biomechanics. It should be noted that recruitment of the virtually cut muscle in Experiment 1 and the actually damaged muscle in Experiment 3 would be associated with substantial energy consumption related to activation (Tsianos et al, 2012), so the observed increase in recruitment is not consistent with minimization of energetic cost. It is possible that the brain has an internal model of the defective muscle but chooses not to use it to optimize energy consumption or that it is unable to make corrections to that internal model within the time frame of these experiments.…”
Section: Does the Brain Maintain And Use A Currently Accurate Internamentioning
confidence: 84%
“…Among different methods for estimating joint torque from muscle activities using electromyography (EMG) are those models that aim at simulating the real physiological processes of the coupling between excitation and contraction (Buchanan et al 2004) and the mechanical application of muscle tension to generate torques (Tsianos et al 2012). Other techniques are based mainly on the associations between measured muscle activities and joint movement (Castellini et al 2009;Seifert and Fuglevand 2002).…”
mentioning
confidence: 99%